Optimizing drip irrigation to enhance winter wheat performance: yield, economic benefits, and water use efficiency - Yanhui Wang; Haowei Sun; Li Wang (International Journal of Agricultural Sustainability)
Drip irrigation is beneficial for improving crop yield and water use efficiency (WUE); however, it is rarely used for winter wheat production in semi-humid and drought-prone areas. To evaluate the optimal drip irrigation amount, a 4-year field experiment was conducted to investigate the effects of applying different water amounts (RF: rainfed; DI1, DI2, and DI3: 60, 120, and 180 mm of drip irrigation; FI3: 180 mm of traditional flood irrigation) on available soil water storage (ASWS), agronomic and physiological characteristics, yield, net income, and WUE of winter wheat in the Guanzhong Plain of China. The results showed that DI2 treatment performed the best among five treatments, which was attributed to the improvement of ASWS consumption in the 1–2 m soil layer, leaf area index, chlorophyll content, and net photosynthetic rate. The four-year average grain yield, net income, and WUE of DI2-treated winter wheat increased by 15.4%, 18.4%, and 25.5%, respectively, compared with FI3. Regression analysis indicated the optimal drip irrigation amounts were 163 and 137 mm in dry and normal years, respectively, and can be considered as a guideline for economical irrigation strategy for winter wheat production in semi-humid and drought-prone areas.